POTENSI PENERIMAAN RETRIBUSI PASAR DI KABUPATEN KETAPANG (KAJIAN TAHUN 2007 2012) - ME, SYARIF MAHADI (Jurnal Ekonomi Daerah (JEDA), 2013)
ABSTRACT This study aims to calculate and determine the magnitude of potential revenues in Ketapang District levy market, knowing the mechanism of implementation of market fee collection in Ketapang district and know the strategies that can be done by natural Ketapang regency government efforts to increase market acceptance in Ketapang district levies. This study uses descriptive and survey research methods. The data analysis technique used is the qualitative and quantitative analysis without the study hypotheses. While data collection techniques were used, namely the field study through interviews and literature study in the form of legislation, reports and other materials derived from the unit of work related to the management of the market in Ketapang District levy. The results showed that the calculation of the estimated potential market tax revenues in Ketapang regency is equal Rp.962.669.085, -. When compared with the determination of the market tax revenue target for 2012 is Rp. 312 521 826, - there is a difference of Rp.650.147.259, - (308.03%). It shows that there is still a market tax revenue base in Ketapang district who have not recorded / maintained in accordance with existing revenue potential, while when compared with the market tax receipts in 2012 amounting to Rp. 290 397 182, - there is a difference of Rp. 672 271 903, - (331.50%). It is shown that the implementation of the realization of market fee collection has not been implemented in accordance with its true potential. For the implementation of the fee collection mechanism in Ketapang market is still not running properly in accordance with applicable regulations. Strategies that should be done by the Government in an attempt to optimize the Ketapang District levy market acceptance in Ketapang District is implementing Regulation on Fees Market through maximization of task and authority management unit market tax levy to increase market acceptance, optimize the role of officers in the collector market withdrawal charges against traders ( compulsory levy), improve coordination and cooperation among related units to make adjustments (improvements / changes) levy is no longer relevant market and apply strict sanctions for merchants (compulsory levy) in violation of applicable regulations. Keywords: Potential Mechanisms and Strategies Markets Levy Increase